Empirical Determinants of US Equity Flows to Developed Countries: Does Valuation Matter? - French, Joseph J. (Universiti Utara Malaysia, 2009)
This paper explores a new panel data set on US gross cross-border equity flows to 20 industrialized nations combined with measures of market valuation for the period of 1977-2005. Empirical evidence of imperfect integration across world equity markets indicates that valuation matters.Consistent with relative value trading as a determinant of equity flow patterns, we find that equity flows decrease sharply with host-country market valuations. This paper also finds that equity flows increase sharply with US equity market valuations. The findings of this research suggest that American investors are informed about both domestic markets and foreign markets. Peripheral findings of this research confirm the findings of other researches, but this research is based on a longer sample period. Consistent with existing literature, there is a negative influence of interest rates spreads, and information asymmetries on cross-border trades in equities.